Seasonal bone mass of college and senior female field hockey players - Beck, B. R.; Doecke, J. D. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The purpose of the study was to observe the relationship of field hockey playing with bone, muscle and fat in young and older adult women. Methods: We measured body composition by dual energy X-ray absorptiometry (DXA) in college players, senior players and controls after a 4-month playing-season and 8-month off-season. Whole body (WB), proximal femur (PF), lumbar spine (LS), right and left forearm (RF, LF) bone mineral density (BMD), percent fat and lean mass of college players (20.6±1.1 years; 7.7±1 playing years) were compared with those of non-playing controls (19.5±1.5 years). BMD of senior players (37.3±10.3 years; 19.7±9.3 playing years) was compared to normative values. The differences between right and left forearm BMDs during the on and off seasons were also compared. Results: College player BMD was higher than controls at the WB (p=0.02), PF (p=0.00004), RF (p=0.006) and LF (p=0.005), but not the LS. Senior player BMD was higher than age-matched norms at the WB (p=0.001) and PF (p=0.006), but not the LS, RF or LF. There were no differences between on and off-season BMDs for either group. There were no differences between college player RF and LF BMD in either season, nor in the senior players during the off-season, however, during the season, senior players developed greater RF than LF BMD (p=0.02). College players had greater lean mass (p=0.00008) and lower fat mass than controls (p=0.003). Neither changed significantly between seasons. Senior players lost fat (p=0.04) and gained lean mass (p=0.02) in season. Conclusion: Adult female field hockey players have higher than average bone mass that does not change significantly according to seasonal involvement.